Upstream-downstream Connectivity: An Overview of Hydrological and Ecological Functions in relation to the Churia-Terai Conservation in Nepal - Paudel, Shambhu; Basnet, Reecha (Forestry: Journal of Institute of Forestry, Nepal, 2018)
The Churia-Terai (CT) is interlinked by the Churia range, Bhabar and Terai, where Terai exist as granary basket of the country and the Churia and Bhabar is the recharge zone of Terai. Changing environment of the Churia range has directly affected the condition of upstream and downstream. To recommend the appropriate watershed management linking upstream and downstream on this landscape, functional analysis were carried out using ecological and hydrological parameters based on secondary literatures. For the proper management of the watershed and its alarming cause of deterioration, understanding upstream and downstream linkages or process is must. Deforestation leads to climate change (temperature and precipitation) and watershed deterioration, which has become the aggravating factor for landslide and soil erosion in upstream and flood in the downstream. The paper highly stressed development of conceptual framework with clear functional activities based on integrated watershed management approach linking the upstream-downstream hydro-ecological phenomena. Thus the paper recommends integrated watershed management with a clear policy which helps to focus priorities and manages its bio-physical condition in a sustainable basis.